Complex interplay of physical forcing and Prochlorococcus population in ocean. (September 2015) - Roy, Rajdeep; Anil, A.C.
Graphical abstract: Highlights: Prochlorococcus occurring in surface water and below oxycline in the northern Arabian Sea represent different ecotypes. Phytoplankton pigment observations revealed contrasting Prochlorococcus distribution before and during convective mixing. Convective mixing disturbs Prochlorococcus niche leading to their disappearance during winter. Seasonal reversal of currents presumably seeds and rejuvenates the Prochlorococcus p opulation. Abstract: Physical forcing can replenish nutrients within the mixed layer by convective mixing or via upwelling. Conventional wisdom holds this enrichment fuels phytoplankton growth, for example ventilation of subsurface water during winter monsoon is known to enhance primary productivity in the northern Arabian Sea. One important numerically dominant phytoplankton known to have ecological niche in the ocean is Prochlorococcus. In the Arabian Sea, they occur in oligotrophic surface water and below the oxycline representing two different light and biogeochemical regimes. Here we show convective mixing in the northern Arabian Sea inhibits Prochlorococcus growth owing to change in physical environment. Pigment observations carried out during early and peak winter monsoon revealed contrasting picoplankton distribution. Divinyl chlorophyll a (a marker for Prochlorococcus ) which was the most abundant picoplankton pigment during early winter monsoon was not detected with the onset of winter convection covarying with high nutrients in the surface water. We propose two possible mechanisms for such sudden disappearance which involves changes in light and biogeochemical regimes. This physico-chemical control could be critical for their existence but not limited to and can play an important role in regions experiencing such phenomenon. We also highlight the linkages between Prochlorococcus succession and basin scale dynamics from the Arabian Sea which hitherto remains poorly understood.